تقييم دور الهيئة الوطنية لترقية العمل ONAPE في دعم المشروعات الصغيرة: المشروعات الصغيرة بمدينة أنجمينا نموذجاً 2016 م. - 2021 م. - آدم، ناصر النائي; داوود، المهدي الغالي; عبدالله، آدم عبدالكريم (الجمعية العلمية للدراسات والبحوث التطبيقية, 2024)
تهدف هذه الدراسة بشكل رئيسي إلى تقييم دور الهيئة الوطنية لترقية العمل ONAPE في دعم المشروعات الصغيرة، وبصفة خاصة المشروعات الصغيرة بمدينة أنجمينا. وتكمن أهمية هذه الدراسة، من أهمية دراسة الموضوع نفسه، الذي يتناول تقييم لدور الهيئة الوطنية لترقية العمل ONAPE في دعم المشروعات الصغيرة، ومعلوم مدى أهمية المشروعات الصغيرة في تحقيق التنمية الاقتصادية والاجتماعية أن هيأ لها المناخ الملائم من حيث التمويل والتدريب والتأهيل، مما يستدعي ضرورة معرفه هل تم لها ذلك، من خلال الدراسة والتقييم لأحد أهم الهيئات التي أنشأتها الدولة لهذا الغرض. وتكمن مشكلة الدراسة في قلة الاهتمام من جانب الدولة التشادية بقطاع المشروعات الصغيرة رغم أهميته من جهة، وضعف الهيئات التي أقيمت مؤخراً بغرض دعم هذه المشروعات الصغيرة من جهة أخرى، زد على ذلك أن هناك ندرة في الدراسات المرتبطة بالموضوع في تشاد، إضافة إلى قصورها وعدم اكتمالها في تحديد درجة كفاءة هيئات التمويل الحكومية وقدرتها على دعم وتنمية قطاع المشروعات الصغيرة في تشاد، من هنا تبرز مشكلة الدراسة في السؤال الرئيسي الآتي: وهو ما مدي مساهمة الهيئة الوطنية لترقية العمل ONAPE في دعم المشروعات الصغيرة بمدينة أنجمينا؟ اعتمدت الدراسة على المنهج الوصفي التحليلي في جمع وتحليل البيانات إضافة إلى المنهج الاستقرائي، من أجل تقييم دور الهيئة الوطنية لترقية العمل ONAPE في دعم المشروعات الصغيرة. ولتحقيق هدف الدراسة، تم تقسيمها بعد مقدمة إلى ثلاثة مباحث وخاتمة، اشتملت على مجموعة من النتائج والتوصيات. Its importance lies in the importance of studying the subject itself, which deals with an evaluation of the role of the National Employment Promotion Office (ONAPE) in supporting small projects. We know how important small-scale projects are in achieving economic and social development if the right environment is created for them in terms of financing, training and qualification, which requires knowing whether they have been. This is done through the study and evaluation of one of the most important organizations created by the State for this purpose. The problem of the study lies in the Chadian state's lack of interest in the small projects sector, despite its importance on the one hand, and its weakness in the organizations recently created to support these small projects on the other, companies, to which is added the scarcity of studies related to this subject in Chad, in addition to their gaps and incompleteness. Government funding bodies support and develop the small-scale project sector in Chad. Thus, the study's problematic is posed in the following main question: What is the extent of the contribution of the National Employment Promotion Office (ONAPE) in supporting small projects in the city of N'djamena? The study used a descriptive analytical approach to data collection and analysis, in addition to an inductive approach, to assess the role of the National Employment Promotion Office (ONAPE) in supporting small projects. To achieve the study's objective, it was divided after an introduction into three sections and a conclusion, which included a set of findings and recommendations.
Keywords: التنمية الاقتصادية -- التمويل الحكومي -- دعم المشروعات الصغيرة -- تشاد